REVISITING INTERRELIGIOUS DIALOGUE IN THE HISTORY OF INDONESIA: The Case of Malino Declaration for Maluku - Hidayati, Mega (EpistemÃƒÂ©: Jurnal Pengembangan Ilmu Keislaman, 2017)
Conflict between Muslims and Christians in Moluccas (1999-2002) is one of the worst conflicts in Indonesia which brings great damage in all fields of human life. The significant result of reconciliation can be found in Central Governmentâs effort called as Malino Declaration II. This paper aims to find a positive contribution on formulating the key for facing the fact of religious plurality in Indonesia by revisiting the Malino Declaration II. By critically analyzing the discourse of the Malino Declaration contents, it concludes that Malino Declaration is shaky for several reason, (1). The role of Government is so dominant, thus Government is in the safe position. Therefore, it isunderstandable why many people view Government aims to âcleanâ its mistakes in the conflict. (2). Military as a tool was not only ineffective and bias, but also it caused mass killings under the banner of national stability. (3) Malino Declaration indicates obviously and strongly that the conflict is pure between Muslim and Christian communities in Moluccas, as the result the blame is theirs, (4) contain of declaration gives an impression that the participants who are representative of each community do not have enough room in expressing and waging in dialogue. In other words, Malino Declaration is still far from genuine dialogue.Konflik antara Muslim dan Kristiani di Maluku (1999-2002) adalah salah satu konflik terburuk di Indonesia yang menyebabkan kerusakan luar biasa di segala bidang kehidupan manusia. Hasil rekonsiliasi yang signifikan adalah usaha pemerintah pusat terkait perumusan Deklarasi Malino II. Dengan meninjau kembali Deklarasi Malino II, tulisan ini bertujuan untuk menemukan kontribusi positif dalam merumuskan kunci dalam menghadapi fakta pluralitas agama di Indonesia. Dengan menganalisis secara kritis isi Deklarasi Malino, dapat disimpulkan bahwa Deklarasi Malino lemah dengan alasan: pertama, peran pemerintah sangat dominan sehingga pemerintah ada di posisi aman. Karenanya, dapat dipahami mengapa banyak orang melihat pemerintah bermaksud âmembersihkanâ kesalahannya dalam konflik tersebut; kedua, militer sebagai alat tidak efektif dan bias serta menyebabkan pembunuhan massa di bawah bendera kestabilan nasional; ketiga, deklarasi Malino mengindikasikan secara jelas dan tegas bahwa konflik tersebut antara komunitas Muslim dan Kristen di Maluku sehingga kesalahan adalah pada kedua kelompok ini; keempat, isi deklarasi memberikan kesan bahwa para partisipan yang mewakili masing-masing komunitas tidak mendapatkan ruang yang cukup dalam mengekspresikan dan melaksanakan dialog. Dengan kata lain, Deklarasi Malino masih jauh dari makna dialog yang sebenarnya.